Exterior characteristics and body measurements of Bligon goat on the different agro-ecological zones in Bantul District, Yogyakarta, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahmawati RD, Atmoko BA, Budisatria IGS, Ngadiyono N, Panjono. 2021. Exterior characteristics and body measurements of Bligon goat on the different agro-ecological zones in Bantul District, Yogyakarta, Indonesia. Biodiversitas 23: 143-150. The Bligon goat is one of the goat breeds those farmers mostly keep in Bantul District, Yogyakarta, Indonesia. This study was conducted to determine the exterior characteristics of Bligon goat in different agro-ecological zones in Bantul District. A total of 478 Bligon goats taken from highlands (146 head), lowlands (163 head), and coastal (169 head) were observed and grouped by age (0-6 months), young (6-18 months), and adults (>18 months). The data observed included qualitative traits (body color distribution and ear shape) and quantitative traits (withers height, chest girth, body length, ear length, and body weight). Qualitative data were analyzed descriptively, and quantitative data were analyzed using one-way analysis of variance. The results showed that the head hair coat color of Bligon goats was mostly striped (pied), with the percentages in the highland, lowland, and coastal zones being 71.9%, 69.2%, and 67.7%, respectively. The body hair coat color in the highland (52.1%) and lowland (39.6%) were striped primarily, while on the coast, it was white (70.7%). The crest color in the highland (69.9%) and lowland (44.7%) were mostly a mixture of brown, black, and white, while on the coast, it was white (70.1%). The mane ruff (rewos) color in the highland (88.4%), lowland (57.9%), and coast (59.3%) were primarily a mixture of brown, black, and white. Ear shapes in the highland (92.5%) and lowland (73.6%) are open principally, while in the coastal areas are mostly folded (56.9%). The average body size of Bligon goats in the coastal zone was larger than in the lowlands (P
Keywords: Bligon goat; Indonesian goat; qualitative traits; quantitative traits